Weak Antilocalization in Polycrystalline SnTe Films Deposited by Magnetron Sputtering - Xiaodong Li; Yang Yang; Xiaocui Wang; Peng Zhu; Fanming Qu; Zhiwei Wang; Fan Yang (Crystals, 2022)
Previous works on weak antilocalization (WAL) of SnTe were mostly carried out in MBE-grown films, where the signals of WAL usually coexist with a large parabolic background of classical magnetoresistance. In this article, we present our study on WAL in polycrystalline SnTe films deposited by magnetron sputtering. Due to the polycrystalline nature and the relatively low mobility of the films, the background of conventional magnetoresistance was greatly suppressed, and clean WAL signals, which are well described by the Hikami–Larkin–Nagaoka equation, were obtained at low temperatures. A close analysis of the WAL data shows that the number of transport channels contributing to WAL increases monotonously with decreasing temperatures, reaching <semantics>N=2.8</semantics> at <semantics>T=1.6</semantics> K in one of the devices, which indicates the decoupling of Dirac cones at low temperatures. Meanwhile, as the temperature decreases, the temperature dependence of phase coherence length gradually changes from <semantics>lϕ∼T−1</semantics> to <semantics>lϕ∼T−0.5</semantics>, suggesting that the dominant mechanism of phase decoherence switches from electron–phonon scattering to electron–electron scattering. Our results are helpful for understanding the quantum transport properties of SnTe.